Taxonomy, abundance and distribution of fishes in the Agos River, Central Sierra Madre, Luzon, Philippines - Carumbana, Esther E. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2002)
The fishes of the Agos River in the Central Sierra Madre (Luzon, Philippines) were surveyed from 1996 to 1998. The ichthyofauna consists of 53 species belonging to 38 families dominated by mullets (Mugilidae, 19.2%), slipmouths (Leiognathidae, 16.4%), gobioids (Gobiidae), 14%) and jacks or trevallies (Carangidae, 8.5%). Thirty seven (69.9%) of the fish species are marine or brackishwater species that spend only part of their life in freshwater while 10 (18.9%) are truly freshwater and six (11.3%) are migratory species.